Christ and evolution: wonder and wisdom - Deane-Drummond, Celia (Fortress Press, 2009)
Christology and evolution as theodrama -- Christology secularised: a theological engagement with evolutionary psychology -- Christ as divine : incarnate wisdom -- Deep incarnation: Christ, the form of beauty -- Revisiting atonement: the drama of Christ and Shadow Sophia -- The risen Christ: a Sophianic interpretation -- Revisiting the new community: Christ in eschatological wonder -- The future of the human: transhuman evolution or human identity as imago Christi?